(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the clinical applicability, examination techniques and compare the US with other body composition methods, to elucidate its potentials and limitations. Methods: Studies were selected in which echography was used in parallel with computed tomography, magnetic resonance, DEXA, bioimpedance, or anthropometry and that included young adults in their sample. The search for articles was performed in Pubmed, Science Direct, Web of Science, Scopus, and BVS databases. Results: 2120 articles were found in the databases and after the evaluation steps, 30 articles were part of the review. In general, the US showed a good correlation with other body composition methods. In muscle assessment, the quantitative assessment with the measurement of muscle thickness or area showed better results. The authors obtained a strong correlation with MRI using measurements of 9 muscle groups (r=0.96 and r=0.91) for men and women, respectively. Qualitative assessment, due to muscle echogenicity, had weaker correlations. A sample studying the reliability and validity of US against MRI reports moderate reliability, with an interclass correlation coefficient ranging from 0.42 to 0.44. Assessing subcutaneous adipose tissue, the studies also showed good results, even measuring adipose tissue in only two body regions, the results were consistent with DEXA (r=0.947) for men and (r=0.909) for women. Conclusion: ultrasound is a useful method for estimating adipose tissue and muscle tissue, showing a good correlation with the most widely used methods of body composition.